In Vitro Conservation of Medicinally Important Climbing Shrub Maerua Arenaria Hook. F. and Thomson - Thirupathi, K.; Ghani, Md.; Suresh, V.; Swamy, T. N.; Rajender, G.; Mustafa, Md. (International Journal of Scientific Research in Biological Sciences, 2019)
Caper family belongs to the order Brassicales comprises various important medicinal plants distributed in tropical countries. Maerua is the second largest genera in this family. Maerua arenaria is a wild climbing shrub having high medicinal value, due to over exploitation it becomes threatened. In vitro propagation technique has been adopted for conserving the valuable medicinal plant by using plant growth regulators. Initially the nodal explants were inoculated on MS medium supplemented with 4.0 mg/l BAP and 2.0 mg/l NAA for axillary bud proliferation. Multiple shoots (5-6 shoots per explant) were recorded after 34 days on MS medium with 2.0 mg/l BAP and 2.0 mg/l IAA. Since the shoots are small, they were transferred on MS medium containing 2.0 mg/l BAP and 2.0 mg/l GA3 for shoot elongation. These well developed elongated shoots were transferred to MS medium supplemented with 2.0 mg/l IBA for rooting. These in vitro developed plantlets were acclimatized in green house and successfully transplanted to natural condition and 78% of plants were survived.